Optimalisasi Pengelolaan BMN Dalam Meningkatkan Kualitas Pelayanan Pada UIN Sumatera Utara Medan - Nur Fadhilah Ahmad Hasibuan (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2023)
The management of State-Owned Goods is highly necessary with the aim of organizing and managing state-owned goods within the university environment to achieve the implementation and good management of state-owned goods in accordance with government regulations, thus achieving the optimization of State-Owned Goods management in the university environment. This study employs a qualitative descriptive approach. The object of the study is the management of State-Owned Goods with the subjects being the university community, namely students and State-Owned Goods managers. Data collection techniques include observation, interviews, and documentation, with data analysis techniques in the form of reduction and analysis. The results of this study indicate that the optimization of State-Owned Goods management in improving campus services at the State Islamic University of North Sumatra is still not optimal. The large number of facilities that are slow to maintain and repair make students feel uncomfortable in the campus environment. Although the management of state-owned goods has implemented regulations related to State-Owned Goods management, it has not yet had a significant impact on the campus community, especially for students.